Preparation method and application of layered double-metal hydroxide modified charcoal material

By growing layered bimetallic hydroxides in situ on the surface of biochar, modifying biochar materials were prepared, which solved the problem of low efficiency and susceptibility to interference when removing low concentrations of PFOS, and achieved efficient and economical PFOS removal effect.

CN119869458APending Publication Date: 2025-04-25NANJING INST OF ENVIRONMENTAL SCI MINIST OF ECOLOGY & ENVIRONMENT OF THE PEOPLES REPUBLIC OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510257042.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When removing low-concentration PFOS, the existing adsorbents have problems such as long adsorption equilibrium time, low adsorption amount to low-concentration PFOS, and are susceptible to other anions in water. The new adsorbents are expensive and difficult to produce in industrial use.

Method used

Layered bimetal hydroxide modified biochar material is prepared by combining aluminum salts and divalent metal ions (such as magnesium, nickel, zinc) with biochar and urea to promote in situ growth of layered bimetal hydroxide (LDH) on the surface of biochar.

Benefits of technology

It realizes efficient removal of low-concentration PFOS, and has anti-interference ability during the removal process, and is low in cost, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869458A_ABST
    Figure CN119869458A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a layered double-metal hydroxide modified biochar material, and the preparation method comprises the following steps: step 1, adding a first metal salt into an aqueous solution containing biochar, stirring and reacting for 65-75 hours, and then adding a second metal salt to obtain a mixed solution; step 2, weighing a certain amount of urea and adding the urea into the mixed solution to obtain a material solution; step 3, putting the material solution into a reaction kettle, and putting the reaction kettle into a drying oven for standing, so as to obtain a turbid liquid; step 4, centrifuging the turbid liquid to obtain a solid, washing the solid with distilled water, and drying the obtained solid to obtain a dried material; and step 5, grinding and sieving the dried material to obtain the layered double-metal hydroxide modified charcoal material. According to the method, the characteristic that the biochar adsorbs cations is utilized, LDH grows on the surface of the biochar in situ under a high-temperature reaction, and the LDH modified biochar material with high removal capacity on low-concentration PFOS is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to a preparation method and application of a layered double metal hydroxide modified biochar material. Background Art

[0002] Perfluoroalkyl Substances (PFAS) are widely used in fire extinguishing agents, aviation hydraulic oils, and non-stick coating production. They are a new class of persistent organic pollutants with characteristics such as chemical stability and difficulty in degradation. They are called "permanent chemicals." Currently, PFAS are found to be widely present in environmental media such as soil, surface water, and groundwater, and have a certain degree of bioaccumulation. They may pose a great safety hazard to human health and the ecological environment, and have received close attention from researchers internationally.

[0003] At present, the main methods for removing PFAS include microbial degradation, ultrasonic degradation, advanced oxidation degradation, photocatalytic degradation, mechanical ball milling and adsorption removal. Among them, adsorption removal is a simple and effective remediation method, but the current commercial adsorbents based on activated carbon and anion exchange resin have the disadvantages of long adsorption equilibrium time, low adsorption of low-concentration PFOS, and strong interference from other anions in water. New adsorbents such as metal organic frameworks and fluoride ion imprinted materials are expensive and difficult to produce industrially. Therefore, obtaining efficient, cheap and green adsorbents is the key to solving the problem of low-concentration PFOS removal.

[0004] Biochar is a cheap adsorption material with a wide range of applications in the adsorption field. However, since it is generally negatively charged, it is difficult to adsorb PFOS, which is also an anion, and has better adsorption performance for cations. Layered double hydroxide (LDH) is an anionic clay mineral composed of hydroxyl-coordinated layer metal cations and interlayer anions. It has a wide range of research and application foundations in the field of environmental remediation, especially its positively charged properties. After it is combined with biochar, it can neutralize the negative charge of biochar, and is expected to enhance the adsorption capacity of PFOS on the surface of biochar. However, the adsorption equilibrium time of adsorption materials based on activated carbon and anion exchange resin is long, and PFOS is greatly affected by anions in other environments, such as sulfate, carbonate and chloride ions. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a preparation method and application of layered double metal hydroxide modified biochar material, which can achieve efficient removal of low-concentration PFOS and have a certain anti-interference ability to other anions.

[0006] The technical solution of the present invention is: a method for preparing a layered double metal hydroxide modified biochar material, comprising the following steps:

[0007] Step 1, adding a first metal salt to an aqueous solution containing biochar, stirring and reacting for 65 to 75 hours, and then adding a second metal salt to obtain a mixed solution; wherein the first metal salt is an aluminum salt, and the second metal salt is a nickel salt, a magnesium salt, or a zinc salt;

[0008] Step 2, weighing a certain amount of urea and adding it to the mixed solution so that the total molar ratio of urea to the metal ions in the mixed solution is 4 to 6, to obtain a material solution;

[0009] Step 3, putting the material solution into a reaction kettle, and placing it in an oven at 90-110° C. for 20-25 hours to obtain a suspension;

[0010] Step 4, centrifuging the suspension to obtain a solid, washing the solid with distilled water for 3 to 4 times, and drying the obtained solid to obtain a dried material;

[0011] Step 5: Grind the dried material through a 100-mesh sieve to obtain a layered double metal hydroxide-modified biochar material.

[0012] Furthermore, the biochar raw material is mulberry straw.

[0013] Description: Mulberry straw has a natural fiber structure and is easy to form a developed pore structure, thus providing an ideal adsorption site for LDH modification. Its pore structure can physically intercept PFOS. After metal modification, it can enhance the adsorption of PFOS through coordination, electrostatics and other effects.

[0014] Furthermore, the total molar concentration of the metal ions in the first metal salt and the metal ions in the second metal salt is 0.12-0.24 mol / L, the molar ratio of the metal ions in the second metal salt to the metal ions in the first metal salt is 1-3, and the biochar addition amount is 1-10 g / L.

[0015] Description: By taking advantage of the characteristics of biochar adsorbing cations, the biochar is first adsorbed with Al 3+ Using the adsorbed biochar as the substrate, Mg, Ni or Zn metal ions and urea were added, and LDH was grown in situ on the biochar surface under high temperature reaction. The obtained LDH-modified biochar material can achieve efficient removal of low-concentration PFOS.

[0016] Furthermore, in step 4, the obtained solid is dried at 80° C. for 8 to 12 hours.

[0017] Note: Through the above drying time and temperature treatment, the solid can be effectively dried to remove residual moisture in the solid, providing dry grinding raw materials for subsequent grinding processing.

[0018] The present invention also provides another biochar, wherein the biochar is activated mulberry straw biochar, and the preparation method of the activated mulberry straw biochar is:

[0019] 1) mulberry straw and 0.5 mol / L citric acid solution are wet-milled to a fineness of 180-240 meshes at a solid-liquid ratio of 1 g:2-5 mL to obtain a pulverized product; lignin depolymerization and cellulose activation are simultaneously achieved through a mechanochemical reaction;

[0020] 2) immersing the crushed product in 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, wherein the mass ratio of the crushed product to the 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid is 1:4-6, and treating the product in a 2300-2500 MHz microwave field for 10-20 minutes to obtain an impregnated product; utilizing the microwave thermal effect to accelerate the penetration of the ionic liquid into the fiber pores and dissolve the hemifiber components;

[0021] 3) treating the impregnated product at a temperature of 70-85° C. and a pressure of 0.2-0.4 MPa for 8-12 min; then raising the temperature to 125-145° C. and the pressure to 1.1-1.4 MPa for 5-10 min, and then raising the temperature to 170-190° C. and the pressure to 0.5-1 MPa for 2-5 min to obtain a hot-pressed product; the fiber structure is softened by hot pressing in the first stage, directional channels are formed by hot pressing in the second stage, and the three-dimensional skeleton is fixed by hot pressing in the third stage to form a stable porous structure and improve the structural strength;

[0022] 4) placing the hot pressed product in a dielectric barrier discharge device with an argon / oxygen mixed atmosphere, introducing an argon / oxygen mixed gas, and treating for 35 to 45 minutes to obtain activated mulberry straw biochar, wherein the power of the dielectric barrier discharge device is 200 to 280 W, and the volume ratio of argon to oxygen is 94 to 96:4 to 6; forming micron-scale pits and nano-scale cracks on the particle surface to enhance the LDH modification effect.

[0023] Description: The above method realizes molecular-level modification through mechanochemical synergy, adopts ionic liquid instead of strong acid and strong base pretreatment agent, and can improve the structural strength of activated mulberry straw biochar through gradient-controlled hot pressing molding, thereby solving the problem of low biochar molding strength. The activated mulberry straw biochar prepared by the present invention can have more attachment points, thereby enhancing its effect as a raw material for layered double hydroxide modified biochar material, and obtaining a layered double hydroxide modified biochar material with more significant low-concentration PFOS removal effect.

[0024] Furthermore, in the step 1), the mulberry straw and 0.5 mol / L citric acid solution are wet-milled at a solid-liquid ratio of 1 g: 2 to 5 mL. During the wet ball milling, a microwave field is applied with a pulse parameter of 700 to 900 W at an interval of 3 to 6 s / time. After the mulberry straw is crushed to a fineness of 80 to 120 mesh, the pulse parameter is adjusted by reducing the power by 20 to 50 W / time until the mulberry straw is crushed to a fineness of 180 to 240 mesh to obtain a crushed product.

[0025] Description: By integrating a microwave generator in the ball mill and applying a microwave field to the wet ball-milled mixture in a pulsed mode, the solvent permeability can be enhanced, the dissociation of the lignin-carbohydrate complex can be promoted, and the synergistic effect of the mechanochemical reaction can be enhanced. By dynamically adjusting the pulse parameters according to the fineness of the wet ball-milled mixture, the effects of lignin depolymerization and cellulose activation can be further enhanced, thereby obtaining activated mulberry straw biochar with better performance.

[0026] Furthermore, the citric acid solution also contains 0.1-0.2% rhamnolipid and 0.05-0.1% polyethylene glycol 6000.

[0027] Description: By adding a certain amount of rhamnolipid and polyethylene glycol 6000 to the citric acid solution, the liquid-solid interfacial tension can be reduced, the nano-particle dispersion system can be stabilized, and the microwave field can be used to enhance the depolymerization of lignin and the activation of cellulose, thereby improving the performance of the prepared activated mulberry straw biochar.

[0028] The present invention also provides an application of a layered double metal hydroxide modified biochar material, wherein the layered double metal hydroxide modified biochar material is used for treating low-concentration PFOS-contaminated water.

[0029] Furthermore, the method for treating low-concentration PFOS-contaminated water using the layered double hydroxide-modified biochar material is as follows: based on a PFOS concentration of 20 to 200 μg / L, the dosage of the layered double hydroxide-modified biochar material to PFOS wastewater is 0.5 to 3.0 g / L.

[0030] Note: By using the above dosage to modify the layered double hydroxide biochar material for the treatment of low-concentration PFOS-contaminated water, PFOS pollution can be effectively removed, and a certain degree of inorganic anion influence can be resisted when removing low-concentration PFOS.

[0031] The beneficial effects of the present invention are:

[0032] The present invention utilizes the characteristic of biochar adsorbing cations, firstly adsorbing Al 3+Taking the adsorbed biochar as the substrate, divalent metal ions (Mg or Ni or Zn) and urea are added. Under high temperature reaction, LDH grows in situ on the surface of biochar to obtain LDH-modified biochar material, which has a high removal ability for low-concentration PFOS. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a microscopic morphology image (1.00 μm) of the layered double metal hydroxide modified biochar material of the present invention.

[0034] Figure 2 It is a microscopic morphology image (5.00 μm) of the layered double metal hydroxide modified biochar material of the present invention. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below in conjunction with specific implementation methods to better reflect the advantages of the present invention.

[0036] Example 1: Layered double metal hydroxide modified biochar material is a biochar material modified by layered double metal hydroxides with Mg and Al as layer metals and carbonate as interlayer anions. The biochar raw material is mulberry straw and is prepared by an in-situ oxygen exposure-spraying method. The specific preparation method includes the following steps:

[0037] Step 1, adding a first metal salt to an aqueous solution containing biochar, stirring the reaction for 72 hours, and then adding a second metal salt to obtain a mixed solution; wherein the first metal salt is aluminum chloride, and the second metal salt is magnesium chloride;

[0038] The total molar concentration of the metal ions (aluminum ions) in the first metal salt and the metal ions (magnesium ions) in the second metal salt is 0.18 mol / L, and the molar ratio of the metal ions (magnesium ions) in the second metal salt to the metal ions (aluminum ions) in the first metal salt is 2, that is, the molar concentration of the metal ions (magnesium ions) in the second metal salt is 0.12 mol / L, the molar concentration of the metal ions (aluminum ions) in the first metal salt is 0.06 mol / L, and the biochar dosage is 3 g / L;

[0039] Step 2, weighing a certain amount of urea and adding it to the mixed solution so that the total molar ratio of urea to the metal ions in the mixed solution is 5, to obtain a material solution;

[0040] Step 3, placing the material solution into a reaction kettle, and placing it in an oven at 100° C. for 24 hours to obtain a suspension;

[0041] Step 4, centrifuging the suspension to obtain a solid, washing the solid with distilled water for 4 times, and drying the obtained solid at 80° C. for 10 h to obtain a dried material;

[0042] Step 5: Grind the dried material through a 100-mesh sieve to obtain a layered double metal hydroxide-modified biochar material.

[0043] Example 2: This example is different from Example 1 in that aluminum salt is added to the aqueous solution containing biochar, and nickel salt, magnesium salt or zinc salt is added after stirring the reaction for 65 hours to obtain a mixed solution.

[0044] Example 3: This example is different from Example 1 in that aluminum salt is added to the aqueous solution containing biochar, and nickel salt, magnesium salt or zinc salt is added after stirring the reaction for 75 hours to obtain a mixed solution.

[0045] Example 4: This example differs from Example 1 in that the total molar concentration of the metal ions (aluminum ions) in the first metal salt and the metal ions (magnesium ions) in the second metal salt is 0.12 mol / L, and the molar ratio of the metal ions (magnesium ions) in the second metal salt to the metal ions (aluminum ions) in the first metal salt is 1, that is, the molar concentration of the metal ions (magnesium ions) in the second metal salt is 0.06 mol / L, and the molar concentration of the metal ions (aluminum ions) in the first metal salt is 0.06 mol / L, the biochar addition amount is 1 g / L, and the total molar ratio of urea to the metal ions in the mixed solution is 4.

[0046] Example 5: This example differs from Example 1 in that the total molar concentration of the metal ions (aluminum ions) in the first metal salt and the metal ions (magnesium ions) in the second metal salt is 0.24 mol / L, and the molar ratio of the metal ions (magnesium ions) in the second metal salt to the metal ions (aluminum ions) in the first metal salt is 3, that is, the molar concentration of the metal ions (magnesium ions) in the second metal salt is 0.18 mol / L, and the molar concentration of the metal ions (aluminum ions) in the first metal salt is 0.06 mol / L, the biochar dosage is 10 g / L, and the total molar ratio of urea to the metal ions in the mixed solution is 6.

[0047] Example 6: This example is different from Example 1 in that the material solution is put into a reaction kettle, placed in an oven at 90°C and allowed to stand for 20 hours to obtain a suspension.

[0048] Example 7: This example is different from Example 1 in that the material solution is put into a reaction kettle, placed in an oven at 110°C and allowed to stand for 25 hours to obtain a suspension.

[0049] Example 8: This example is different from Example 1 in that the suspension is centrifuged to obtain a solid, and the solid is washed three times with distilled water. The obtained solid is dried at 80° C. for 8 h to obtain a dried material.

[0050] Example 9: This example is different from Example 1 in that the suspension is centrifuged to obtain a solid, and the solid is washed 4 times with distilled water. The obtained solid is dried at 80° C. for 12 h to obtain a dried material.

[0051] Example 10: This example is different from Example 1 in that the biochar used is activated mulberry straw biochar, and the preparation method of the activated mulberry straw biochar is as follows:

[0052] 1) mulberry straw and 0.5 mol / L citric acid solution were wet-milled to a fineness of 220 meshes at a solid-liquid ratio of 1 g:4 mL to obtain a pulverized product; lignin depolymerization and cellulose activation were simultaneously achieved through a mechanochemical reaction;

[0053] 2) immersing the crushed product in 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, the mass ratio of the crushed product to the 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid being 1:5, and treating it in a 2450MHz microwave field for 15 minutes to obtain an impregnated product; utilizing the microwave thermal effect to accelerate the ionic liquid to penetrate the fiber pores and dissolve the semi-fiber components;

[0054] 3) treating the impregnated product at a temperature of 80°C and a pressure of 0.3MPa for 10 minutes; then raising the temperature to 130°C and the pressure to 1.3MPa for 8 minutes, and then raising the temperature to 180°C and the pressure to 0.8MPa for 3 minutes to obtain a hot-pressed product; the fiber structure is softened by hot pressing in the first stage, directional channels are formed by hot pressing in the second stage, and the three-dimensional skeleton is fixed by hot pressing in the third stage to form a stable porous structure and improve the structural strength;

[0055] 4) The hot pressed product was placed in a dielectric barrier discharge device with an argon / oxygen mixed atmosphere, and an argon / oxygen mixed gas was introduced for 42 minutes to obtain activated mulberry straw biochar; wherein the power of the dielectric barrier discharge device was 260 W, and the volume ratio of argon to oxygen was 95:5, forming micron-scale pits and nano-scale cracks on the particle surface to enhance the LDH modification effect.

[0056] Example 11: This example is different from Example 10 in that the mulberry straw and 0.5 mol / L citric acid solution are wet-milled to a fineness of 180 mesh at a solid-liquid ratio of 1 g:2 mL.

[0057] Example 12: This example is different from Example 10 in that the mulberry straw and 0.5 mol / L citric acid solution are wet-milled to a fineness of 240 mesh at a solid-liquid ratio of 1 g:5 mL.

[0058] Example 13: This example is different from Example 10 in that the crushed product is immersed in 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, the mass ratio of the crushed product to 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid is 1:4, and is treated in a 2300 MHz microwave field for 10 minutes to obtain an infiltrated product.

[0059] Example 14: This example differs from Example 10 in that the crushed product is immersed in 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, the mass ratio of the crushed product to 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid is 1:6, and is treated in a 2500 MHz microwave field for 20 minutes to obtain an infiltrated product.

[0060] Example 15: The difference between this example and Example 10 is that the impregnated product is treated at a temperature of 70°C and a pressure of 0.2 MPa for 8 min; then the temperature is raised to 125°C, the pressure is raised to 1.1 MPa, and the treatment is carried out for 5 min; then the temperature is raised to 170°C, and the pressure is raised to 0.5 MPa for 2 min to obtain a hot pressed product.

[0061] Example 16: The difference between this example and Example 10 is that the impregnated product is treated at a temperature of 85°C and a pressure of 0.4 MPa for 12 min; then the temperature is raised to 145°C and the pressure is raised to 1.4 MPa for 10 min, and then the temperature is raised to 190°C and the pressure is raised to 1 MPa for 5 min to obtain a hot pressed product.

[0062] Example 17: The difference between this example and Example 10 is that the hot-pressed product is placed in a dielectric barrier discharge device with an argon / oxygen mixed atmosphere, and an argon / oxygen mixed gas is introduced for 35 minutes to obtain activated mulberry straw biochar, wherein the power of the dielectric barrier discharge device is 200 W, and the volume ratio of argon to oxygen is 94:6.

[0063] Example 18: The difference between this example and Example 10 is that the hot-pressed product is placed in a dielectric barrier discharge device with an argon / oxygen mixed atmosphere, and an argon / oxygen mixed gas is introduced for 45 minutes to obtain activated mulberry straw biochar, wherein the power of the dielectric barrier discharge device is 280 W, and the volume ratio of argon to oxygen is 96:4.

[0064] Example 19: The difference between this example and Example 10 is that, in the step 1), the mulberry straw and 0.5 mol / L citric acid solution are wet-milled at a solid-liquid ratio of 1 g:4 mL. During the wet ball milling, a microwave field is applied with a pulse parameter of 850 W and an interval of 5 s / time. After the product is crushed to a fineness of 100 mesh, the pulse parameter is adjusted by reducing the power by 40 W / time until the product is crushed to a fineness of 220 mesh to obtain a crushed product.

[0065] Example 20: This example is different from Example 19 in that a microwave field is applied at a pulse parameter of 700 W at an interval of 3 s / time, and after the powder is crushed to a fineness of 80 mesh, the pulse parameter is adjusted by reducing the power by 50 W / time until the powder is crushed to a fineness of 180 mesh to obtain a crushed product.

[0066] Example 21: This example is different from Example 19 in that a microwave field is applied with a pulse parameter of 900 W and an interval of 6 s / time. After the powder is crushed to a fineness of 120 mesh, the pulse parameter is adjusted by reducing the power by 20 W / time until the powder is crushed to a fineness of 240 mesh to obtain a crushed product.

[0067] Example 22: This example is different from Example 19 in that the citric acid solution further contains 0.15% rhamnolipid and 0.08% polyethylene glycol 6000.

[0068] Example 23: This example is different from Example 22 in that the citric acid solution further contains 0.1% rhamnolipid and 0.05% polyethylene glycol 6000.

[0069] Example 24: This example is different from Example 22 in that the citric acid solution further contains 0.2% rhamnolipid and 0.1% polyethylene glycol 6000.

[0070] Example 25: This example also provides an application of a layered double hydroxide modified biochar material based on Example 1 or 2, wherein the layered double hydroxide modified biochar material is used for the treatment of low-concentration PFOS-contaminated water. Specifically, the method for using the layered double hydroxide modified biochar material for the treatment of low-concentration PFOS-contaminated water is as follows: based on a PFOS concentration of 150 μg / L, the dosage of the layered double hydroxide modified biochar material to the PFOS wastewater is 1.5 g / L.

[0071] Example 26: This example is different from Example 25 in that, based on a PFOS concentration of 20 μg / L, the dosage of the layered double hydroxide modified biochar material to the PFOS wastewater is 0.5 g / L.

[0072] Example 27: This example is different from Example 25 in that, based on a PFOS concentration of 200 μg / L, the dosage of the layered double hydroxide modified biochar material to the PFOS wastewater is 3.0 g / L.

[0073] Application experiment example:

[0074] 1. Implementation case of adsorbent adsorbing low concentration PFOS

[0075] The adsorbent dosage was 1.5 g / L, the PFOS concentration was 150 μg / L, and the solid was filtered after reacting for 30 minutes. Among them, the NiAl / biochar was based on Example 1, and magnesium chloride was replaced by nickel chloride; the ZnAl / biochar was based on Example 1, and magnesium chloride was replaced by zinc chloride; the PFOS removal rate is shown in Table 1:

[0076] Table 1 Removal rate of PFOS in water

[0077]

[0078]

[0079] It can be seen from the results in Table 1 above that the biochar materials modified with layered double hydroxides having Ni or Mg or Zn and Al as layer metals and carbonate as interlayer anions in the present invention all have good PFOS removal effects.

[0080] 2. Implementation case of adsorbent adsorption of low concentration PFOS to resist anion interference

[0081] Taking MgAl-LDH / biochar as an example, the adsorbent dosage is 3.0 g / L, the mixed PFOS concentration is 200 μg / L, the chloride ion, nitrate ion, sulfate ion and bicarbonate ion concentration are 1 mg / L respectively, and the solid is filtered after reacting for 30 minutes. The removal rate of PFOS is shown in Table 2:

[0082] Table 2 Removal rate of PFOS by adsorbent in the presence of anions

[0083] ion PFOS removal rate Nitrate 99.20% Chloride ion 99.10% Bicarbonate 98.50% Sulfate 98.60%

[0084] It can be seen from the results in Table 2 above that the prepared MgAl-LDH / biochar has a strong resistance to chloride ions, nitrate ions, sulfate ions and bicarbonate ions, and can resist a certain degree of inorganic anion influence when removing low concentrations of PFOS.

[0085] 3. Implementation cases of various adsorbents for adsorption of low concentration PFOS against anion interference

[0086] From the results of the anti-anion interference of chloride ion, nitrate ion, sulfate ion and bicarbonate ion in 2, it can be seen that the anti-interference of bicarbonate under the interference of four anions is relatively poor, so bicarbonate is used as a comparison indicator; the dosage of each adsorbent is 3.0g / L, the PFOS concentration is 200μg / L, the bicarbonate ion concentration is 1mg / L, and the solid is filtered after 30min of reaction. The PFOS removal rate is shown in Table 3:

[0087] Table 3 Removal rate of PFOS in water

[0088] Adsorption material PFOS removal rate Adsorption material PFOS removal rate Example 2 98.43% Embodiment 14 99.48% Example 3 98.51% Embodiment 15 99.35% Example 4 98.27% Example 16 99.50% Example 5 98.43% Embodiment 17 99.28% Example 6 98.31% Embodiment 18 99.51% Example 7 98.52% Embodiment 19 99.75% Example 8 98.45% Embodiment 20 99.69% Example 9 98.50% Embodiment 21 99.71% Example 10 99.47% Embodiment 22 99.84% Embodiment 11 99.21% Embodiment 23 99.80% Example 12 99.43% Embodiment 24 99.82% Example 13 99.27%

[0089] It can be seen from the results in Table 3 above that the use effects of the layered double hydroxide modified biochar materials prepared in different embodiments are different. The analysis results are as follows:

[0090] 1) Compared with Example 1, the step parameters of the preparation method of the layered double metal hydroxide modified biochar material in Example 2-Example 9 were adjusted. In Examples 2 and 3, different stirring reaction times had a certain effect on the use effect of the mixed solution, among which Example 3 had the best use effect, but it was basically the same as the use effect of Example 1, and the preparation efficiency of Example 1 was higher, so the stirring reaction parameters of Example 1 were relatively better; in Examples 4 and 5, different metal ion concentrations and urea amounts had a certain effect on the use effect of the prepared modified biochar material, among which Example 1 had the best use effect; in Examples 6 and 7, different oven parameters had a certain effect on the use effect of the suspension, among which Example 7 had the best use effect, but it was basically the same as the use effect of Example 1, and the preparation efficiency of Example 1 was higher, so the oven parameters of Example 1 were relatively better; in Examples 8 and 9, different drying parameters had a certain effect on the use effect of the dried material, among which Examples 1 and 9 had the best use effect, but Example 9 used a longer preparation time, so the drying parameters of Example 1 were relatively better.

[0091] 2) In Example 10-Example 18, compared with Example 1, the biochar used was adjusted. After using the activated mulberry straw biochar, the use effect of the modified biochar material prepared in Example 1 was improved to a certain extent; in Examples 11 and 12, different grinding ratios had a certain impact on the effect of mulberry straw in the mechanical chemical reaction to simultaneously achieve lignin depolymerization and cellulose activation, among which the activated mulberry straw biochar prepared in Example 10 had the best use effect; in Examples 13 and 14, different impregnation treatments had a certain impact on the effect of mulberry straw using microwave thermal effect to accelerate the penetration of ionic liquid into fiber pores, among which the activated mulberry straw biochar prepared in Example 10 had the best use effect. The best effect is achieved; in Examples 15 and 16, different gradient hot pressing molding parameters have a certain impact on the structural strength of the activated mulberry straw biochar, among which Example 16 has the best effect, but it is basically the same as the effect of Example 10, and the preparation efficiency of Example 10 is higher, therefore, the gradient hot pressing molding parameters of Example 10 are relatively better; in Examples 17 and 18, different post-treatment parameters have a certain impact on the effect of the activated mulberry straw biochar, among which Example 18 has the best effect, but it is basically the same as the effect of Example 10, and the preparation efficiency of Example 10 is higher, therefore, the post-treatment parameters of Example 10 are relatively better.

[0092] 3) Compared with Example 10, the preparation method of activated mulberry straw biochar used in Example 19-Example 21 is optimized, so that the use effect of the prepared activated mulberry straw biochar is further improved. In Examples 20 and 21, different pulse treatment parameters have a certain impact on the use effect of the activated mulberry straw biochar, among which Example 19 has the best use effect.

[0093] 4) Compared with Example 19, the preparation method of the activated mulberry straw biochar used in Example 22-Example 24 was optimized, so that the use effect of the prepared activated mulberry straw biochar was further improved. In Examples 23 and 24, different citric acid solutions had a certain effect on the use effect of the activated mulberry straw biochar, among which Example 22 had the best use effect.

Claims

1. A method for preparing a layered double metal hydroxide modified biochar material, characterized in that: The following steps are involved: Step 1, adding a first metal salt to an aqueous solution containing biochar, stirring and reacting for 65 to 75 hours, and then adding a second metal salt to obtain a mixed solution; wherein the first metal salt is an aluminum salt, and the second metal salt is a nickel salt, a magnesium salt, or a zinc salt; Step 2, weighing a certain amount of urea and adding it to the mixed solution so that the total molar ratio of urea to the metal ions in the mixed solution is 4 to 6, to obtain a material solution; Step 3, putting the material solution into a reaction kettle, and placing it in an oven at 90-110° C. for 20-25 hours to obtain a suspension; Step 4, centrifuging the suspension to obtain a solid, washing the solid with distilled water for 3 to 4 times, and drying the obtained solid to obtain a dried material; Step 5: Grind the dried material through a 100-mesh sieve to obtain a layered double metal hydroxide-modified biochar material.

2. The method for preparing a layered double metal hydroxide modified biochar material according to claim 1, characterized in that: The biochar raw material is mulberry straw.

3. The method for preparing a layered double metal hydroxide modified biochar material according to claim 1, characterized in that: The total molar concentration of the metal ions in the first metal salt and the metal ions in the second metal salt is 0.12-0.24 mol / L, the molar ratio of the metal ions in the second metal salt to the metal ions in the first metal salt is 1-3, and the biochar addition amount is 1-10 g / L.

4. The method for preparing a layered double metal hydroxide modified biochar material according to claim 1, characterized in that: In the step 4, the solid is washed with distilled water for 3 to 4 times, and the obtained solid is dried at 80° C. for 8 to 12 hours.

5. The method for preparing a layered double metal hydroxide modified biochar material according to claim 1, characterized in that: The biochar is activated mulberry straw biochar, and the preparation method of the activated mulberry straw biochar is as follows: 1) mulberry straw and 0.5 mol / L citric acid solution are wet-milled to a fineness of 180-240 meshes at a solid-liquid ratio of 1 g:2-5 mL to obtain a pulverized product; 2) immersing the crushed product in 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid, wherein the mass ratio of the crushed product to the 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid is 1:4-6, and treating the crushed product in a 2300-2500 MHz microwave field for 10-20 minutes to obtain an infiltrated product; 3) treating the impregnated product at a temperature of 70-85° C. and a pressure of 0.2-0.4 MPa for 8-12 min; then raising the temperature to 125-145° C. and the pressure to 1.1-1.4 MPa for 5-10 min, and then raising the temperature to 170-190° C. and the pressure to 0.5-1 MPa for 2-5 min to obtain a hot pressed product; 4) placing the hot pressed product in a dielectric barrier discharge device in an argon / oxygen mixed atmosphere for 35 to 45 minutes to obtain activated mulberry straw biochar; wherein the power of the dielectric barrier discharge device is 200 to 280 W, and the volume ratio of argon to oxygen is 94 to 96:4 to 6.

6. The method for preparing a layered double metal hydroxide modified biochar material according to claim 5, characterized in that: In the step 1), mulberry straw and 0.5 mol / L citric acid solution are wet-milled at a solid-liquid ratio of 1 g: 2-5 mL. During the wet-milling, a microwave field is applied at a pulse parameter of 700-900 W at an interval of 3-6 s / time. After the mulberry straw is crushed to a fineness of 80-120 meshes, the pulse parameter is adjusted by reducing the power by 20-50 W / time until the mulberry straw is crushed to a fineness of 180-240 meshes to obtain a crushed product.

7. The method for preparing a layered double metal hydroxide modified biochar material according to claim 6, characterized in that: The citric acid solution also contains 0.1-0.2% rhamnolipid and 0.05-0.1% polyethylene glycol 6000.

8. The use of the layered double metal hydroxide modified biochar material prepared by the method according to any one of claims 1 to 7, characterized in that: The layered double metal hydroxide modified biochar material is used for treating low-concentration PFOS-contaminated water.

9. The use of the layered double metal hydroxide modified biochar material as claimed in claim 8, characterized in that: The method for treating low-concentration PFOS-contaminated water using the layered double metal hydroxide modified biochar material is as follows: based on a PFOS concentration of 20 to 200 μg / L, the dosage of the layered double metal hydroxide modified biochar material to PFOS wastewater is 0.5 to 3.0 g / L.